2018
DOI: 10.1021/acs.jpclett.8b02943
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Water Molecules in Quantum Crystals

Abstract: With the use of solid parahydrogen in matrix isolation spectroscopy becoming more commonplace over the past few decades, it is increasingly important to understand the behavior of molecules isolated in this solid. The mobility of molecules in solid parahydrogen can play an important role in the dynamics of the system. Water molecules embedded in solid parahydrogen as deposited were found to be mobile at 4.0 K on the time scale of a few days. The diffusion at this temperature must be due to quantum tunneling in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Moore and co‐workers recently demonstrated that the photodissociation of proteogenic amino acids in the singlet state yields products such as imine derivatives and CO 2 [2] . This formation primarily occurs from HOCO+RCHNH 2 radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moore and co‐workers recently demonstrated that the photodissociation of proteogenic amino acids in the singlet state yields products such as imine derivatives and CO 2 [2] . This formation primarily occurs from HOCO+RCHNH 2 radicals.…”
Section: Resultsmentioning
confidence: 99%
“…Recent investigations by Moore and colleagues have shed light on the UV photodissociation of specific proteogenic amino acids at 193 and 213 nm, leading to fundamental discoveries concerning the nature of the resulting photoproducts [1,2] . Notably, the irradiation of Alanine, Glycine, Leucine, Proline, and Serine produces amino radical (RCHNH 2 ) and hydroxycarbonyl radical (HOCO).…”
Section: Introductionmentioning
confidence: 99%
“…While the large D G values bolster the notion discussed in ref of enhanced Al atom recombination/reaction occurring near pH 2 crystallite grain boundaries during sample deposition, they do not impact the mobility of Al atoms trapped in the grain interiors. Indeed, recent MIS studies of the aggregation of small molecules (e.g., HF and H 2 O) in low temperature pH 2 solids report measurements performed on a timescale of days, not milliseconds. , Finally, the coefficient of self-diffusion in liquid H 2 only reaches D ≈ 0.9 × 10 –4 cm 2 /s near the boiling point at T = 20 K, while radioactive tracer measurements on 85 Kr in liquid H 2 indicate D ≈ 1.5 × 10 –4 cm 2 /s at T = 20 K …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, recent MIS studies of the aggregation of small molecules (e.g., HF and H 2 O) in low temperature pH 2 solids report measurements performed on a timescale of days, not milliseconds. 36,37 Finally, the coefficient of self-diffusion in liquid H 2 only reaches D ≈ 0.9 × 10 −4 cm 2 /s near the boiling point at T = 20 K, 38 while radioactive tracer measurements on 85 Kr in liquid H 2 indicate D ≈ 1.5 × 10 −4 cm 2 /s at T = 20 K. 39 Thus, our calculated lower limit on the diffusion coefficient of D > 6 × 10 −4 cm 2 /s is not consistent with Al atom diffusion in solid or even liquid pH 2 . Because this value rests on a single observation, it should rightly be viewed with much skepticism.…”
mentioning
confidence: 99%
“…In terms of more classical guest species like an oxygen atom, even less is known. Further complicating our understanding of guest diffusion in solid p-H 2 is that both HF and H 2 O have been reported to quantum-diffuse in solid p-H 2 . This was unexpected, and there still is no definitive explanation of how the HF and H 2 O molecules diffuse through the p-H 2 matrix host.…”
Section: Introductionmentioning
confidence: 99%